100PConcordance between tissue analysis (TA) and liquid biopsy (LB) for RAS/BRAF and the optimization of its clinical application in such a heterogeneous tumour. (7th November 2019) - Grilo, I; Leite, R; Gago, P; Duarte, S; Teira, A; Sarmento, T; Sousa, M
Abstract: Background: In metastatic CRC, the absence of RAS/BRAF mutation is indicative of a good response to anti-EGFR therapy. However, these patients have a distinct genomic profiles and tumors heterogeneity. This is probably the greatest difficulty regarding the detection of mutations in tumor tissue. LB can overcome this, detecting cDNA as well as early changes in mutational status before the clinical progression. Dynamic molecular analysis may allow new therapeutic sequences. Methods: Non-randomized observational study since October 2014 - ongoing, for evaluation concordance of RAS/BRAF status between LB and TA and monitoring every 8 weeks using the Idylla MT, in patients with metastatic CRC. Results: 148 liquid biopsies corresponding to 101 patients have been performed until now. Verification of concordance was possible only in 54 patients due to missions tissue biopsy (done outside the institution). The overall agreement was 70.2% (47/61), with 44.7% mutRAS patients. When we look at patients with liver metastasis, the agreement increases to 89%. Disagreement was found in 14 patients, and in 29.6%(4/14) TA was WT and LB mutRAS. When we reviewed the patients reassessed with LB at 8 weeks, 3 changed their status from mutated to WT. It was also found that one patient, initially WT treated with anti-EGFR in LB, was detected Gly12Ala / Gly12Val mutation, and in 2nd LB it was WT. Another patient initially detected A146P/T/V mutation was treated with oral fluropyrimidine, becoming WT in LB, progressed and started doublet+bevacizumab with partial response, and the same mutation was detected in 2 nd LB. Conclusions: It appears that the site of metastases (liver, peritoneum, lung) has an impact on the detection of RAS/BRAF cDNA status. In cases of RAS/BRAF WT in TA, LB may better predict the response to anti-EGFR agents. In these preliminary results, the tumor has been shown to be clearly dynamic; the change of mutated RAS/BRAF status to WT was confirmed during the instituted therapy, opening a possible therapeutic window the for these patients with anti-EGFR therapy. This study included so far a small sample but demonstrates that personalized therapy with molecular/genomic analysis is undoubtedly valuable. Legal entity responsible for the study: CHTMAD - Onco-Hematology Department. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.